(untitled) (Raparin Journal of Humanities (RJH), 2022)
Sexual harassment is a form of gender-based violence and discrimination that includes any explicit or implicit act of a sexual nature , that is unwelcome or undesirable, in such a way that the other person feels insulted, humiliated or threatened or fear. This study attempts to answer a basic question: Is there sexual harassment of women at work? And if so, what are the main causes? The main objective of this study is to find out the amount of sexual harassment directed against women working in all the existing institutions, For this reason, the researcher used a sample of (300) units at random to carry out the operation procedures, but after returning the forms, only (268) units admitted that they were harassed during work Therefore, the researcher applied all statistical processes to this sample, One of the most important conclusions that the researcher reached after analyzing the scale form: The majority of women who were subjected to sexual harassment were between (31-50) years old, and most of them were unmarried and married, they worked in government institutions, and the majority of them were harassed by co-workers inside the institution, Verbal harassment, such as talking about jokes and sexual stories, is one of the most common types of harassment that the majority of the sample members were subjected to, One of the most important causes of sexual harassment, as indicated by the majority of the sample, is addiction to pornographic films , One of the most important effects of sexual harassment on the victim is exposing her to fear, anxiety, and loss of confidence in herself and others, The sample members used their friends to help them get rid of the harasser as one of the methods of confrontation, and in the end, the researcher suggested carrying out intensive campaigns in order to educate all members of society about the seriousness of this phenomenon and for all existing devices and even legislators to take a serious action to confront it.